2020
DOI: 10.1055/s-0039-3400480
|View full text |Cite
|
Sign up to set email alerts
|

Update on Lung Cancer Screening

Abstract: Over the past 10 years, there has been substantial progress in the study and implementation of lung cancer screening using low-dose computed tomography (LDCT). The National Lung Screening Trial, the recently reported NELSON (NEderlands-Leuvens Longkanker Screenings ONderzoek) trial, and other European trials provide strong evidence for the efficacy of LDCT to reduce lung cancer mortality. This has resulted in the United State's Preventative Task Force and numerous professional medical societies adopting lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…According to epidemiology reports on non-small cell lung cancer (NSCLC), cancer-related deaths mostly occur in people over the age of 65 years (2). With the introduction of lung cancer screening programs with low-dose chest computed tomography (CT) scans, thoracic surgeons frequently encounter incidental findings of lung lesions suspected of malignancy (e.g., solid lesions >8 mm or subsolid lesions ≥ 6 mm), which require subsequent percutaneous transthoracic needle biopsy for selected populations (3). However, percutaneous biopsy may not provide findings for semi-solid or pure ground-glass nodules, and surgeons cannot access central or perivascular lesions because of serious fatal complications associated with percutaneous procedures (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…According to epidemiology reports on non-small cell lung cancer (NSCLC), cancer-related deaths mostly occur in people over the age of 65 years (2). With the introduction of lung cancer screening programs with low-dose chest computed tomography (CT) scans, thoracic surgeons frequently encounter incidental findings of lung lesions suspected of malignancy (e.g., solid lesions >8 mm or subsolid lesions ≥ 6 mm), which require subsequent percutaneous transthoracic needle biopsy for selected populations (3). However, percutaneous biopsy may not provide findings for semi-solid or pure ground-glass nodules, and surgeons cannot access central or perivascular lesions because of serious fatal complications associated with percutaneous procedures (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Our data are in line with previous studies, which observed similar percentages of QFT conversion (11%). 4 Hence, we believe that even in areas with low TB prevalence, annual QFT testing remains a useful and mandatory tool to avoid eventual TB reactivation in patients with psoriasis undergoing anti-TNF-a therapy. However, owing to the possibility of the reinfection risk being different in diverse areas, more studies are needed to confirm our results (including studies from countries with a dissimilar incidence of TB infection).…”
mentioning
confidence: 99%
“…3 For example, annual lung cancer screening is not recommended in all smokers, but specifically for older smokers who have accumulated numerous smoking pack-years. 4 Furthermore, it is important to consider other intrinsic screening-test characteristics, including sensitivity, costs and the consequences of false-positive results. 3 As Megna et al acknowledge, some of their cohort patients who 'converted' to a positive QFT result may have been falsely positive.…”
mentioning
confidence: 99%
“…3 For example, annual lung cancer screening is not recommended in all smokers, but specifically for older smokers who have accumulated numerous smoking pack-years. 4 Furthermore, it is important to consider other intrinsic screening-test characteristics, including sensitivity, costs and the consequences of false-positive results. 3 As Megna et al acknowledge, some of their cohort patients who 'converted' to a positive QFT result may have been falsely positive.…”
mentioning
confidence: 99%